The “Written procedure safe based work” to improve the safety and occupational health of the small underground mining - Ponce E., Victor (2018)
The objective of this study is to determine the incidence of PETS-Base with occupational health and safety in the Small Underground Mining, case of the Arequipa M Unit of the Caudalosa Mining Company, 2015; It is a descriptive, cross-sectional investigation with a descriptive-correlational design. With the survey technique, a Likert questionnaire of 31 questions was applied to 25 people in charge of the application of the PETS-Base, the information was processed with the SPSS v.21. The results indicate a level of significance of Sig = 0.00124665 and a rho of Spearman, r = 0.782. Concluding that there is a positive and significant relationship between the PETS-Base with Occupational Safety and Health in the workers of the Small Underground Mining, case of the Arequipa M Unit of the Caudalosa Mining Company, 2015; recommending an innovative attitude of the PETSBase and of the prevention programs of risks and damages in the workers of the underground mines.